Short term outcomes after extreme preterm birth in England: comparison of two birth cohorts in 1995 and 2006 (the EPICure studies). (4th December 2012) - Costeloe, Kate L; Hennessy, Enid M; Haider, Sadia; Stacey, Fiona; Marlow, Neil; Draper, Elizabeth S
Abstract : Objective To determine survival and neonatal morbidity for babies born between 22 and 26 weeks' gestation in England during 2006, and to evaluate changes in outcome since 1995 for babies born between 22 and 25 weeks' gestation. Design Prospective national cohort studies. Setting Maternity and neonatal units in England. Participants 3133 births between 22 and 26 weeks' gestation in 2006; 666 admissions to neonatal units in 1995 and 1115 in 2006 of babies born between 22 and 25 weeks' gestation. Main outcome measures Survival to discharge from hospital, pregnancy and delivery outcomes, infant morbidity until discharge. Results In 2006, survival of live born babies was 2% (n=3) for those born at 22 weeks' gestation, 19% (n=66) at 23 weeks, 40% (n=178) at 24 weeks, 66% (n=346) at 25 weeks, and 77% (n=448) at 26 weeks (P<0.001). At discharge from hospital, 68% (n=705) of survivors had bronchopulmonary dysplasia (receiving supplemental oxygen at 36 weeks postmenstrual age), 13% (n=135) had evidence of serious abnormality on cerebral ultrasonography, and 16% (n=166) had laser treatment for retinopathy of prematurity. For babies born between 22 and 25 weeks' gestation from March to December, the number of admissions for neonatal care increased by 44%, from 666 in 1995 to 959 in 2006. By 2006 adherence to evidence based practice associated with improved outcome had significantly increased. Survival increased from 40% to 53% (P<0.001) overall and at each week of gestation: by 9.5% (confidence interval −0.1% to 19%) at 23 weeks, 12% (4% to 20%) at 24 weeks, and 16% (9% to 23%) at 25 weeks. The proportions of babies surviving in 2006 with bronchopulmonary dysplasia, major cerebral scan abnormality, or weight and/or head circumference <−2 SD were similar to those in 1995, but the proportion treated for retinopathy of prematurity had increased from 13% to 22% (P=0.006). Predictors of mortality and morbidity were similar in both cohorts. Conclusion Survival of babies born between 22 and 25 weeks' gestation has increased since 1995 but the pattern of major neonatal morbidity and the proportion of survivors affected are unchanged. These observations reflect an important increase in the number of preterm survivors at risk of later health problems.